Impact of ASEAN Plus Five Free Trade Area: Trade Creation and Trade Diversion - Sony Vebiyanto; Hastarini Dwi Atmanti (Jurnal Ekonomi Pembangunan, 2022)
One of the ways to reduce international trade barriers is through the Free Trade Area (FTA). Collectively, ASEAN already has five FTAs with trading partners outside Southeast Asia. This study intends to analyze the effect of free trade agreements between ASEAN and China, South Korea, Japan, India, and Australia – New Zealand (ASEAN+5 FTA). The implications of an FTA are explained using the concepts of trade creation and trade diversion through economic integration. The trade gravity model is expanded with three dummy variables to determine whether trade creation and trade diversion occur in the formation of each of these FTAs. Static panel data regression is used to analyze the effect of Free Trade Agreements on intra-regional trade flows, export flows to non-members, and import flows from non-FTA members. The fixed effect model is applied to overcome endogeneity problems, while the PPML estimator is chosen to get the best estimation results amid heteroscedasticity and zero trade flow problems that usually occur in trade flows. Estimation results show that the trade creation effect occurs only in ACFTA and AIFTA, while other FTAs harm member countries through trade diversion. Therefore, further evaluation and efforts regarding the use of FTAs are needed to achieve the goals of FTAs.